Perancangan Awal Perangkat Lunak Ensiklopedia Wayang Digital Berbasis Multimedia - Purnama, Bambang Eka (Speed - Sentra Penelitian Engineering dan Edukasi, 2010)
One of the usage of computer technology is as information media and data processing which is communicative interaktif and familiar for the society of amendable consumer toward multimedia. Multimedia is colaboration from various element which consist of text, graphical, animation, video and voice. By using computer touch hence will be got by result of much more maximal than by manual. Microsoft Visual Basic is an application package alternative which can be used programming by exploiting database. Merger of Ianguage of programming system and of multimedia which is sinergis expected will be able to yield maximal application and interactive. So that consumer can chosen shares and appearance of another wanted without difficulty. This research aim to water down in giving other alternative and picture to consumer society that result of data processing of multimedia can colaboration with programming language. Besides result of which is got will be able to just enjoy by whom. Consumer of computer alone alternatively, giving the understanding of to puppets actor or even to wishful any person who study programming language, art and multimedia of culture puppets. Made system rely on data bases object and graphical appearance of multimedia. So that with data which have on file will be able to be processed according to need and can be processed furthermore again for certain strategic . Made system can work well at computer with Pentium I 133 MHz prosesor or newer or another compatibel, with minimum memory 16 MB or more and VGA card 1 MB or more.